Solar-powered cold storage for fruits and vegetable vendors - Yamauchi, Futoshi (CGIAR System Organization, 2024)
Full solar-powered walk-in cold stations for the 24/7 storage and preservation of fruits and vegetables, located at markets, ideal for vendors/retailers to store their produce. The cold storage prevents post-harvest losses, i.e. prolonging the shelf-life, nutritional and economic value of the perishable produce. The cold station is run as a business, with the storage service being priced per space and time of storage. The facility is guarded 24/7 and can be accessed during work hours.